The rape of Europa in Ancient Literature: from the Hellenistic period to Late-antiquity (Circe de clásicos y modernos, 2024)
The present work aims to explore a series of constituent elements of the myth of the rape of Europa in the versions of Moshus (Europa), Ovid (Metamorphosis 2. 833-875 and 6. 103-107; Fasti 5. 603-620), Achilles Tatius (Leucippe and Clitophon 1), Lucian of Samosata (“Zephyrus and Notus”, Dialogues of the Sea Gods) and Nonus of Panopolis (Dionysiaca 1). The objective is to try to determine the source(s) that each author could have used, based on the mention or omission of some of these components in the different rewritings, as well as the changes in the way they are used.
Keywords: Europa; Moschus; myth; abduction; meadow